The Diversity of Grasshoppers in Liwa Botanical Garden Based on Time Capture - Alita Nur Afdila; M. Kanedi; Nismah Nukmal; Sutyarso Sutyarso (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
Grasshopper is one of the diurnal cosmopolitan insect, the existence of grasshoppers is very influential for some other animal populations such as birds. It is still lack of information of diversity, distribution, population, and other basic biological aspects of grasshoppers at Kebun Raya Liwa (KRL). To monitor biodiversity, it is necessary to provide informations about the number of individuals, their functions, and roles in the habitat and ecosystem. Therefore it is necessary to conduct the research of these topics. This research was carried out during November to December 2019, at the Taman Hias Kebun Raya Liwa. Grasshoppers were cached in the morning from 06.00 AM to 09.00 AM, day from 10.00 AM to 02.00 PM, and afternoon from 03.00 PM to 06.00 PM . The grasshoppers was cached using a sweeping net by exploring the Taman Hias Kebun Raya Liwa. The caught grasshopper was identified at the Zoology Laboratory of the Faculty of Mathematics and Natural Sciences, Universitas Lampung. The result show that ten species of grasshopper were found at the Taman Hias Kebun Raya Liwa, i.e. Phaleoba antennata, Phaleoba fumosa, Phaleoba rustica, Atractomorpha crenulata, Atractomorpha sp., Phillium crurifolium, Phillium sp, Trilophidia annulata, Oxya chienensis, and Melanoplus differentialentialis. The index diversity of grasshopper at the Taman Hias Kebun Raya Liwa is categorized to moderate with H' = 2.223. The best time to catch grasshoppers is in the morning from 06.00 AM-09.00 AM and afternoon from 03:00 PM – 05:00 PM.